SYSTEMATIC LITERATURE REVIEW: FINANCIAL LITERACY, TECHNOLOGY, AND CORPORATE GOVERNANCE FOR MSMEs REPORTING QUALITY - Faiz Ramli Pratama; Angelia Angelia; Citra Aprilia; Iqlima Nurhaliza; Safina Andam Dewi; Christyan Dumawan (Profit: Jurnal Kajian Ekonomi dan Perbankan Syariah)
Micro, Small, and Medium Enterprises (MSMEs) often struggle to produce quality financial reports due to limited financial literacy, inadequate use of technology, and weak corporate governance practices. These limitations hinder transparency, reduce accountability, and restrict access to external funding. This study aims to explore the contribution of financial literacy, technology adoption, and corporate governance to the quality of financial reporting among MSMEs. Using a Systematic Literature Review (SLR) approach, the study analyzed 13 peer-reviewed articles published between 2020 and 2025. The review followed the PRISMA protocol and applied a thematic analysis framework based on Agency Theory. The findings reveal that while each factor such as financial literacy, technology, and governance have a positive impact, their integration plays a more significant role in improving the accuracy, transparency, and accountability of MSME financial reports. The study concludes that a combined approach involving knowledge, digital tools, and internal control mechanisms is essential to strengthening the trust of external stakeholders and enhancing the financial credibility of MSMEs